Penilaian Guru Bahasa Indonesia Pada Kompetensi Keterampilan Menyimak di Era Pandemi Covid-19 di SMP Negeri Sekecamatan Rambah Hilir - Tiwi, Pratiwi Sri Rahmadani; Sukenti, Desi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
The research is entitled ''Assessment of Indonesian Language Teachers on Listening Skills Competence in the Era of the Covid-19 Pandemic in State Junior High Schools in Rambah Hilir District''. Problem formulation, how is the assessment of Indonesian language teachers on listening skill competencies in State Junior High Schools throughout the Rambah Hilir District during the Covid-19 pandemic? and What are the difficulties experienced by Indonesian language teachers in planning learning assessments on listening skill competencies in the Covid-19 pandemic era at State Junior High Schools in Rambah Hilir District? The purpose of this study was to determine the assessment of Indonesian language teachers on listening competence at State Junior High Schools throughout the Rambah Hilir District during the Covid-19 pandemic. and find out the difficulties experienced by Indonesian language teachers in planning learning assessments on listening competence in the Covid-19 pandemic era at State Junior High Schools in Rambah Hilir District. The research method is phenomenology, qualitative type. The theory used in this study is the notion of assessment, learning outcomes assessment function, teaching assessment evaluation, listening competence, listening objectives, listening assessment. The data sources of this research are 6 Indonesian language teachers. Data collection techniques include observation, in-depth interviews and documentation. The data analysis technique groups the similarity of meanings in the assessment research of Indonesian language teachers on listening skill competencies at State Junior High Schools in Rambah Hilir District. The results of the research on the assessment of Indonesian language teachers on the competence of listening skills for fable text material were assessed from concluding, writing conclusions, writing descriptions, listening, paragraphs, story conclusions, concluding the content of conversations, answering questions, extrinsic intrinsic elements, listening and listening, vocabulary. The conclusion of the research on the assessment of Indonesian language teachers on the competence of listening skills in the era of the covid-19 pandemic in State Junior High Schools in Rambah Hilir District, the text of the fable story is thirteen sub-themes.